The Emergence of Multi-Messenger Astronomy, Part II: A Socio-Epistemic Network Analysis of Scientific Literature, 1997-2023. - LALLI, ROBERTO; BONOLIS, LUISA; LA RANA, ADELE (Centaurus: Journal of the European Society for the History of Science, 2025)
After exploring the role of supernova research--understood as epistemic laboratories--in the later emergence of multi-messenger astronomy in the first part, this second article of our two-part study examines the rise and consolidation of the research field in the 21st century. Although often heralded as a novel and transformative approach, multi-messenger astronomy has roots in the convergence of earlier practices such as multi-wavelength astronomy, astroparticle physics, and gravitational-wave detection, each with their own distinct and evolving scientific subcultures. The study explores how these traditions coalesced, analyzing the processes that linked subcommunities and the roles of institutional frameworks, scientific collaboration, and thematic integration in shaping the field. The paper combines quantitative analysis of scientific literature with the close reading of strategically selected scientific publications. Network science tools are employed in an exploratory fashion to trace patterns of collaboration and the evolution of research topics. We argue that the scientific literature explicitly framing itself as multi-messenger astronomy can be divided into three periods. The exploratory phase (1997-2008) saw very few papers using the term, largely within nascent programs in very-high-energy gamma-ray astronomy and astroparticle physics. During the emergence phase (2009-2015), researchers pursued the conceptual and operational integration of astroparticle physics in anticipation of the advent of gravitational-wave astronomy, with gamma-ray studies emerging as a central connecting research field in the network. Finally, the consolidation phase (2016-2023) was sparked by the first direct detection of gravitational waves and saw the realization of the multi-messenger observational programs previously envisioned. Our analysis reveals, first, that astroparticle physics served as the cradle of the multi-messenger approach--initially integrating high-energy neutrinos, cosmic rays, and gamma rays, and later incorporating gravitational waves both conceptually and, following their detection, empirically into a unified framework. Second, we show that forward-looking imaginaries--particularly the anticipation of gravitational-wave discoveries--profoundly shaped research practices and priorities.